Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.31004/obsesi.v7i1.2947
|View full text |Cite
|
Sign up to set email alerts
|

Apakah Kebersyukuran dan Persepsi Dukungan Organisasi Berperan dalam Meningkatkan Kebahagiaan Guru TK?

Abstract: Kebahagiaan guru TK merupakan salah satu kunci keberhasilan pendidikan anak, tetapi, jika guru memiliki masalah personal dan masalah organisasi dapat  menyebabkan menurunnya kebahagiaan yang dirasakan. Tujuan penelitian ini untuk menguji pengaruh kebersyukuran dan persepsi dukungan organisasi terhadap kebahagiaan guru taman kanak-kanak di Purwokerto. Penelitian ini menggunakan metode kuantitatif kolerasional.  Populasi sebanyak 310 guru taman kanak-kanak Purwokerto dengan sampel 167 yang dipilih dengan teknik … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
3
0
1
Order By: Relevance
“…The study by Ravina-Ripoll et al (2022) discovered a structural equation model that identified the parameters of academic satisfaction, organizational climate, and affective commitment as recommended for assessing the happiness of future police inspectors. Rosita et al (2023) research also found that teachers can achieve happiness if they have personal factors, such as gratitude. Gratitude can generate positive emotions, thus contributing to individual happiness.…”
Section: Introductionmentioning
confidence: 88%
“…The study by Ravina-Ripoll et al (2022) discovered a structural equation model that identified the parameters of academic satisfaction, organizational climate, and affective commitment as recommended for assessing the happiness of future police inspectors. Rosita et al (2023) research also found that teachers can achieve happiness if they have personal factors, such as gratitude. Gratitude can generate positive emotions, thus contributing to individual happiness.…”
Section: Introductionmentioning
confidence: 88%
“…Ini melibatkan pengembangan kebiasaan positif serta konsistensi dalam menjalankan tugas-tugas dan tanggung jawab. Terdapat beberapa cara yang dapat membantu individu membangun disiplin diri yaitu pertama rutinitas harian yang sehat (Dini, 2023).…”
Section: Tantangan Dalam Proses Transformasi Diri Melalui Proses Islahunclassified
“…In this case, it is said that individuals with high happiness and gratitude have a smaller chance of experiencing burnout Gratitude is an important aspect of the foundation of a healthy mental life including avoiding the problem of academic burnout (Sood in Wibowo & Mulawarman, 2022). Same exposure to the previous opinion Emmons and Mishra (Manita et al, 2019) revealed that the basis of well-being and mental health over the life span is gratitude (Anas in Rosita et al, 2023) explained that the concept of gratitude is a tendency to give a positive response to experiences experienced and the perceived impact. Students who have a sense of gratitude tend to appreciate positive things in their learning environment, not only in school but also in home environment, togetherness with friends, existing teachers and their learning outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…McCullough, Emmons and Tsang (in Rosita et al, 2023) describe aspects of gratitude consisting of intensity, frequency, span, and density. Intensity is a person's gratitude after experiencing a positive event in his life.…”
Section: Introductionmentioning
confidence: 99%